A distinctive patchy osteomalacia characterises Phospho1‐deficient mice. Issue 2 (August 2017) - Boyde, Alan; Staines, Katherine A.; Javaheri, Behzad; Millan, Jose Luis; Pitsillides, Andrew A.; Farquharson, Colin
Abstract: The phosphatase PHOSPHO1 is involved in the initiation of biomineralisation. Bones in Phospho1 knockout (KO) mice show histological osteomalacia with frequent bowing of long bones and spontaneous fractures: they contain less mineral, with smaller mineral crystals. However, the consequences of Phospho1 ablation on the microscale structure of bone are not yet fully elucidated. Tibias and femurs obtained from wild‐type and Phospho1 null (KO) mice (25–32 weeks old) were embedded in PMMA, cut and polished to produce near longitudinal sections. Block surfaces were studied using 20 kV backscattered‐electron (BSE) imaging, and again after iodine staining to reveal non‐mineralised matrix and cellular components. For 3D characterisation, we used X‐ray micro‐tomography. Bones opened with carbide milling tools to expose endosteal surfaces were macerated using an alkaline bacterial pronase enzyme detergent, 5% hydrogen peroxide and 7% sodium hypochlorite solutions to produce 3D surfaces for study with 3D BSE scanning electron microscopy (SEM). Extensive regions of both compact cortical and trabecular bone matrix in Phospho1 KO mice contained no significant mineral and/or showed arrested mineralisation fronts, characterised by a failure in the fusion of the calcospherite‐like, separately mineralising, individual micro‐volumes within bone. Osteoclastic resorption of the uncalcified matrix in Phospho1 KO mice was attenuated compared with surrounding normally mineralised bone. The extent and position of this aberrant biomineralisation varied considerably between animals, contralateral limbs and anatomical sites. The most frequent manifestation lay, however, in the nearly complete failure of mineralisation in the bone surrounding the numerous transverse blood vessel canals in the cortices. In conclusion, SEM disclosed defective mineralising fronts and extensive patchy osteomalacia, which has previously not been recognised. These data further confirm the role of this phosphatase in physiological skeletal mineralisation.